CORAK TAFSIR MAQASIDI DALAM TAFSIR AL-TAHRIR WA AL-TANWIR - Laila, Alviga Nur; Ochviardi, Danang (JIQTA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
Ibn ‘Ashur was a famous commentator in the 14th century H. The book Tafsir al-Tahrir wa al-Tanwir by Ibn ‘Ashur was the leading tafsir in Tunis. The book of Tafsir Ibn ‘Ashur is classified as a moderate commentary. In interpreting the Qur'an, Ibn ‘Ashur was more inclined to use ratios compared to the Prophet's interpretation. For the reason that there are far more verses that have not been interpreted by the Prophet than those that have been interpreted, so it is necessary to hold ijtihad. The Book of Tafsir al-Tahrir wa al-Tanwir is not only an interpretation of the Al-Qur'an, but also a linguistic book. This book of tafsir is used by tafsir scholars, especially in analyzing the language of the verses of the Koran. The aim of this research is to determine the style of interpretation of maqasidi in the book of tafsir al-Tahrir wa al-Tanwir. The method used by the author for this research is a literature review (library research). There are those who think that Ibn 'Ashur's interpretation is based on ijtima'i adab, in his interpretation he focuses on revealing the balaghah and miracles of the Qur'an in explaining the meaning and content in accordance with natural law, improving the social life of the people, and so on.